The Implementation Model for the Process Islamic Religious Education (PAI) in 6 Senior High School of Palembang - Marlina, Leny (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the management of the implementation of the process of Islamic religious education (PAI) in 6 senior high schools in Palembang. The research method is qualitative. This type of intrinsic case study research is qualitative with the logic of inductive thinking. The research findings found that in addition to the three activities, there is a synergy between the intracurricular activities and extracurricular activities of Islamic religious education (PAI) in schools that support each other, and there is a common vision of all school members to build an Islamic environment. The three activities in the implementation of Islamic religious education (PAI) have a significant role in the implementation of the educational process, specifically Islamic religious education.